The taming of prices: Framing and fighting inflation in the second half of the twentieth century in Argentina - Mariana Heredia; Claudia Daniel (economic sociology_the european electronic newsletter, 2019)
Historians agree that bringing inflation under control became a crucial challenge for western governments in the 1970s and opened a space for experimentation to neoliberal policy. But inflation did not appear out of the blue with the oil crises. Widespread price rises were a current and persistent phenomenon since the postwar years. The difference was that interventionist states had managed to keep it contained and considered inflation to be a minor problem compared to growth, employment, and distribution. In contrast, from the 1970s price increases climbed and the battle against inflation became one of the main public and political concerns...
Keywords: 330